Os dois lados do technostress: uma perspectiva a partir do uso do Instagram - Marco, Daiana de (2023)
The present study aimed to investigate the Techno Eustress and Techno Distress resulting from the use of Instagram, understanding how the factors that promote Techno Eustress manifest themselves and investigating strategies to cope with Techno Distress used by independent workers. Through Instagram, independent workers can create visually appealing content, share relevant information about their products or services, and establish a closer, more personal relationship with their audience. Technostress can be understood as the positive (Techno Eustress) and negative (Techno Distress) stress that users face when using the Information System. On the other hand, coping strategies are used to reduce the negative effect and promote the positive effect in relation to the use of technology. To this end, qualitative research was carried out based on interpretative assumptions and template analysis. The corpus of analysis involved 24 interviews with individuals from different areas of activity. The findings demonstrate that in the context of Instagram use, perceptions of the elements that make up the characteristics of the technology were quite diverse. Independent workers realize that Instagram is useful in different ways (publicity, portfolio, connections, marketing, sales, visibility, consolidation of authority and brand). Furthermore, the design is perceived as easy to use, but presents challenges related to reach, engagement and the algorithm. The technostressor of technical support challenge did not prove to be a motivating factor for the use of Instagram. Additionally, negative feelings do not appear to be directly related to the techno-complexity of the platform, but rather to the expectation that the platform will work as expected. Technoinsecurity involved new elements such as concerns about reach, metrics, rejection, lack of control and engagement expectations. Technological overload and techno-invasion were permeated by the constant need to be connected and maintain an active presence on the platform. The lack of a contingency strategy and the difficulty in adhering to other platforms are worrying threats to the permanence of independent workers in the digital environment. However, it is noticeable that workers continually adapt to changes on the platform, learning and improving their skills, and flexibility also stimulates the creativity of this audience, encouraging them to innovate through the platform's resources. In this way, creativity is seen as a crucial element to stand out and adapt in a constantly evolving online environment, such as Instagram. Problem-focused coping strategies are used to find a healthy balance between work and personal life, as well as the need for planning and control to deal with stress. Furthermore, the use of strategies focused on emotion provides some changes in the behavior of independent workers, who now adopt a calmer and more understanding approach to the platform.